2012
DOI: 10.1016/j.rbmo.2011.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Meiotic recombination, synapsis, meiotic inactivation and sperm aneuploidy in a chromosome 1 inversion carrier

Abstract: Disrupted meiotic behaviour of inversion carriers may be responsible for suboptimal sperm parameters in these carriers. This study investigated meiotic recombination, synapsis, transcriptional silencing and chromosome segregation effects in a pericentric inv(1) carrier. Recombination (MLH1), synapsis (SYCP1, SYCP3) and transcriptional inactivation (γH2AX, BRCA1) were examined by fluorescence immunostaining. Chromosome specific rates of recombination were determined by fluorescence in-situ hybridization. Furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…A possible way to test if a chromosome segment was affected by an inversion is to analyze the pattern of synapsis and crossing over in SC spreads in heterozygotes. Extensive analyses of SC spreads in plants, mice and humans carrying inversions have shown that these rearrangements can lead to synaptic irregularities, loop formation and disruption of the normal crossover pattern [Ashley et al, 1981;Moses et al, 1982;Gabriel-Robez et al, 1986;Anderson et al, 1988;Koehler et al, 2004;Massip et al, 2010;Kirkpatrick et al, 2012].…”
Section: © 2015 S Karger Ag Baselmentioning
confidence: 99%
“…A possible way to test if a chromosome segment was affected by an inversion is to analyze the pattern of synapsis and crossing over in SC spreads in heterozygotes. Extensive analyses of SC spreads in plants, mice and humans carrying inversions have shown that these rearrangements can lead to synaptic irregularities, loop formation and disruption of the normal crossover pattern [Ashley et al, 1981;Moses et al, 1982;Gabriel-Robez et al, 1986;Anderson et al, 1988;Koehler et al, 2004;Massip et al, 2010;Kirkpatrick et al, 2012].…”
Section: © 2015 S Karger Ag Baselmentioning
confidence: 99%
“…The reduction/suppression of COs within inversions is well documented across several organisms [12, 13]. Different mechanisms are invoked to explain this CO suppression such as non-homologous synapsis (hetero-synapsis) [32] and asynapsis [16] between the normal and inverted regions. However, in this work recombination events such as double COs are detected in chromosome 3 suggesting that homo-synapsis occurs in the rearranged region.…”
Section: Discussionmentioning
confidence: 99%
“…One of these mechanisms operates through inversions, which are strong suppressors of recombination across the rearranged chromosomal regions [12]. Reduction/suppression of COs in inverted regions is reported in various organisms including yeast [13], C. elegans [14], mammals [15, 16] and plants [1719]. Inversions have been studied extensively in multiple Drosophila species [20].…”
Section: Introductionmentioning
confidence: 99%
“…The detection of particular breakpoint sites can be correlated with a degree of spermatogenic failure in male carriers. The inv(1) carrier displayed synapsis impairment for all unsynapsed bivalents exhibiting markers of transcriptional silencing, which may cause impaired spermatogenesis [Kirkpatrick et al 2012]. A meiotic failure could be due to a reduction in recombination events with an absence of a full loop formation and the rare occurrence of a partial loop leading [Chandley et al 1987].…”
Section: Discussionmentioning
confidence: 99%